Potential of Cognitive Management and Value-communicative Nature of University Education - Dmitry A. Belyaev; Olga A. Volkova; Evgenia P. Shebolkina (Высшее образование в России)
The article provides an overview of foreign and national research on the possibilities of using cognitive management in the educational environment of higher education institution. The authors emphasize the potential of cognitive management principles application in the educational organization, the direct correlation between cognitive management tasks and the general purposes of educational process. The possible approaches to knowledge management in educational organization are described. The authors dwell on the general methodological, economic and functional aspects of cognitive management at the university, argue that the value-communicative essence of university education enables to manage the knowledge base of the university. On the example of Ukhta State Technical University the article considers the possibilities of students’ project activity and project self-government. Firstly, it ensures the increment and intensification of the value-communicative flow of knowledge within the University and in its interaction with the external environment. Secondly, it fosters students to master the role of a cognitive manager. Thirdly, it encourages students to develop their meta-abilities which can be viewed as a form of cognitive management outcomes in higher educational institution.